2019
DOI: 10.1111/jphp.13178
|View full text |Cite
|
Sign up to set email alerts
|

Total flavones of Rhododendron simsii Planch flower protect rat hippocampal neuron from hypoxia-reoxygenation injury via activation of BKCa channel

Abstract: Objectives To study the effects of total flavones of Rhododendra simsii Planch flower (TFR) on hypoxia/reoxygenation (H/R) injury in rat hippocampal neurons and its underlying mechanism. Method Model of H/R was established in newborn rat primary cultured hippocampal neuron. Lactate dehydrogenase (LDH) and neuron‐specific enolase (NSE) activity as well as malondialdehyde (MDA) content in cultured supernatants of the neurons were examined. Methyl thiazolyl tetrazolium assay and Hoechst33258 staining were, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Therefore, it could be concluded that phosphorylation of ROCK 2 at Tyr722 also mediates protective effect of H 2 S against H/R injury in RHNs. It was well-known that inhibition of the RhoA-ROCK signaling pathway protects cerebral ischemia-reperfusion injury [ 34 , 35 ]. Combined with the above-mentioned that H 2 S promotes the phosphorylation of ROCK 2 at Tyr722 to inhibit ROCK 2 activity in RHNs, our results demonstrated that H 2 S protects RHNs from H/R injury through promoting phosphorylation of ROCK 2 at Tyr722 to inhibit ROCK 2 activity.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it could be concluded that phosphorylation of ROCK 2 at Tyr722 also mediates protective effect of H 2 S against H/R injury in RHNs. It was well-known that inhibition of the RhoA-ROCK signaling pathway protects cerebral ischemia-reperfusion injury [ 34 , 35 ]. Combined with the above-mentioned that H 2 S promotes the phosphorylation of ROCK 2 at Tyr722 to inhibit ROCK 2 activity in RHNs, our results demonstrated that H 2 S protects RHNs from H/R injury through promoting phosphorylation of ROCK 2 at Tyr722 to inhibit ROCK 2 activity.…”
Section: Discussionmentioning
confidence: 99%
“…For OGD/R (Chen et al, 2013), hippocampal neurons were subjected to 4 h of hypoxia induced by replacing culture medium with glucose‐free D‐Hank's solution (in mg·L −1 : 8000 NaCl, 400 KCl, 510 Na 2 HPO 4 ·12H 2 O, 60 KH 2 PO 4 and 350 NaHCO 3 , pH 7.2–7.4) under the condition of 94% N 2 , 5% CO 2 and 1% O 2 and 24 h of reoxygenation induced by replacing the glucose‐free D‐Hank's solution with normal culture medium and being incubated under normal condition. In NaHS or the other drug treatment groups, cells were respectively treated with NaHS (1 × 10 −6 M) (Wen et al, 2018), iberiotoxin (100 nM) (Guo et al, 2020), BMS‐191011 (10 μM) (Levin et al, 2016), NNC 55‐0396 (100 μM) (Angstadt et al, 2017) or verapamil (100 μM) (Tang et al, 2016) before and during OGD/R.…”
Section: Methodsmentioning
confidence: 99%
“…Luteolin administration alleviated neuroinflammation, oxidative stress and neuronal insulin resistance as well as improved the Morris water maze (MWM) and step-through task and increased the levels of BDNF [ 373 ]. Other effects of flavones described recently are anxiolytic-like activity [ 374 ], neuroprotection against gamma-radiation [ 375 ] treatment of glioblastoma [ 376 ], amelioration of the hypoxia-reoxygenation injury [ 377 ] or inhibition of the neuroinflammation caused by LPS [ 378 ].…”
Section: Flavonesmentioning
confidence: 99%